Analysis on factors controlling organic matter enrichment in marine-terrestrial transitional shale of Member 1, Upper Carboniferous Keluke Formation, Huaitoutala area, east of northern margin of Qaidam Basin, China - Tiangong Lai; Fei Xia; Guangnan Huang; Wenjin Liu; Da Sun; Fanming Meng; Weilong Wang (PLoS ONE, 2025)
The organic-rich shale of the Member 1 of the Keluke Formation (in this paper referred to as Member 1) has been newly discovered as a good source rock reservoir in the western Delingha Depression, Huaitoutala area in the east part of the northern margin of Qaidam Basin, but the factors that control the enrichment of the organic matter in the shale are still unclear. In this paper, the paleo-climate, redox condition, paleo-salinity, hydrothermal activity and primary productivity of the dark shale in Member 1 are studied based on the analysis results of the total organic carbon (TOC), the element geochemistry and the whole rock mineral testing, and the enrichment mechanism of organic matter is discussed. Based on the vertical variation of the TOC contents, the Member 1 shale section is divided into two sub-sections (Sub-section I and Sub-section II), with the TOC content of Sub-section II (avg. 2.79%) being higher than the TOC content of Subsection I (avg. 0.92%). Similarly, the chemical index of alteration (CIA) values of Subsection II are also higher, indicating a hot, warm and humid paleoclimate, whereas the CIA values of Subsection I are low, indicating a rapidly cooling paleoclimate. The ratios of Sr/Ba and Rb/K2O are relatively high, indicating that the paleo-water body of Member 1 was mainly dominated by medium-high salinity water. The fluctuating EFU and EFMo values and the low-moderate ratios of Th/U, V/Cr and Corg/P indicate that the shale was formed in an oxic – dysoxic environment. The slightly higher ratios of Al/(Al + Fe + Mn), the slightly negative Eu anomaly, and the (Cu + Co + Ni)×10-Fe-Mn and Zn-Ni-Co ternary diagrams show that the shale was affected by atypical (weak) hydrothermal activity with relatively high terrigenous clastic input. The P/Al, Cu/Al and Zn/Al ratios show that the primary productivity of the surface water was relatively high with an upward gradually increasing trend. The TOC is significantly correlated with the indicators of palaeo-climate, palaeo-salinity, terrigenous clastic input and primary productivity, indicating that the enrichment of organic matter in the shale of Member 1 is mainly controlled by the high primary productivity, the brackish – salt water environment and the dysoxic preservation condition in a warm and humid climate. In addition, the terrigenous clastic input (adsorption of clay minerals) also plays important roles. Based on these results, a two-section organic matter enrichment model of this Member is established.